2014
DOI: 10.1007/s00125-014-3458-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of fibroblast growth factor 21 with cardiovascular outcome events in the Fenofibrate Intervention and Event Lowering in Diabetes study

Abstract: Aims/hypothesis Circulating fibroblast growth factor 21 (FGF21) levels are often elevated in obesity, dyslipidaemia, insulin resistance and type 2 diabetes. This study investigated the relationship of plasma FGF21 levels with cardiovascular events in patients with type 2 diabetes. Methods Plasma FGF21 levels were measured by ELISA at baseline in 9,697 individuals with type 2 diabetes participating in the Fenofibrate Intervention and Event Lowering in Diabetes (FIELD) study. We assessed the association of FGF21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 44 publications
4
69
1
Order By: Relevance
“…Circulating FGF21 levels were found to be predictive of the primary outcome of total CVD over a median follow‐up of 5 years. However, analyses of secondary outcomes showed that the associations were positive for stroke, coronary, and carotid revascularization, but not CHD events, after adjusting for established CVD risk factors 20. A small study on 87 T2DM subjects from Poland also reported a predictive role of serum FGF21 levels with incident cardiovascular morbidity and mortality over 2 years,24 but no information on the prediction of incident CHD was provided.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Circulating FGF21 levels were found to be predictive of the primary outcome of total CVD over a median follow‐up of 5 years. However, analyses of secondary outcomes showed that the associations were positive for stroke, coronary, and carotid revascularization, but not CHD events, after adjusting for established CVD risk factors 20. A small study on 87 T2DM subjects from Poland also reported a predictive role of serum FGF21 levels with incident cardiovascular morbidity and mortality over 2 years,24 but no information on the prediction of incident CHD was provided.…”
Section: Discussionmentioning
confidence: 98%
“…Serum creatinine was measured and the eGFR was calculated using the Chronic Kidney Disease Epidemiology Collaboration equation as described previously 18. Serum high‐sensitivity C‐reactive protein was measured with a high‐sensitivity, particle‐enhanced immunoturbidimetric assay (Roche Diagnostics, GmbH, Mannheim, Germany) and serum FGF21 was measured with ELISA kits (Antibody and Immunoassay Services, University of Hong Kong, Hong Kong, China) 19, 20…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, baseline plasma samples were available for FGF21 measurement from 9697 (99.0%) out of 9795 patients from the FIELD study. FGF21 levels were measured using enzyme-linked immunosorbent assay kits (Antibody and Immunoassay Services, University of Hong Kong, Hong Kong) as described previously [7,12,17]. Briefly, a 60 μl plasma sample was diluted 1:1 (vol.:vol.)…”
Section: Methodsmentioning
confidence: 99%
“…Other variables of interest The measurement of clinical characteristics and details of the primary endpoint and other outcomes of the FIELD trial have been described previously [9][10][11][12][15][16][17]. Previous CVD comprised angina, myocardial infarction, coronary artery bypass grafting, percutaneous transluminal coronary angioplasty, stroke, peripheral vascular disease and revascularisation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation